The experience and impact of urban floods and pollution in Ebo Town, Greater Banjul Area, in The Gambia - Afi Kavegue; Irit Eguavoen (University of Bonn, Center for Development Research (ZEF), 2016)
The unplanned settlement Ebo Town is flooded almost every year with polluted water from uphill Kanifing Municipality because of a lack of infrastructure for sanitation and drainage. When droughts occurred in the 1970s, destitute people started to move to the peripheral swamp of Tambi Wetland Complex first to cultivate rice and later to settle. Today, after wetland conversion, Ebo Town is blocking the runoff to the lagoon. Most inhabitants subsist on very low incomes. Based on interviews with teachers, school children and their families, the authors analyze how lives and family income change as a result of floods. Accessing school on safe ways may not be possible during the floods and the risk of becoming ill increases. The study also investigates what schools, authorities, parents and external agencies do to improve the situation. The key findings show that Ebo Town residents undertake minor modification on their houses, carry valuable property to safe places and restrict school attendance in order to protect their children from floods and illness. They pursue reactive and concurrent strategies on household level rather than mobilizing the Ebo Town community for more effective action. Many people thought they would not be able to change the situation anyway and waited for government support.
Keywords: 330; urbanization; wetland conversion; flood; disaster; children; storyboard; West Africa; Gambia